Achieving financial stability of Islamic banks through a Bespoke Enterprise Risk Management Framework (ERMF) - Sani Suleiman, Dlhatu; Adam Sa'ad, Auwal; Syed Jaafar Alhabshi, Syed Musa; Bashir Aliyu, Umar (2021)
Definition: Enterprise Risk Management (ERM) —various ways firms keep check on their risks to harness opportunities and attain institutional objectives. ERM Framework (ERMF) —a document aim to set general guidelines for managing risk of events or actions that could result in adverse outcomes for the institution (COSO, 2004)